2020
DOI: 10.1038/s41598-020-58792-z
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors and application prospects of CO2 flooding in heterogeneous glutenite reservoirs

Abstract: horizontal wellbore. With the continuous increase in gas injection, the lower part of the reservoir is gradually displaced, and the final sweep efficiency of gas can exceed 80%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The gas always extracts some components from the oil phase (Boyun et al 2007). Therefore, the efficiency of oil transport by gas can be explained by the concept of MMP (Wang et al 2020). When the gas injection is maintained above the MMP, a high oil recovery factor is achieved (Bisweswar et al 2020).…”
Section: Results Of Comparative Simulation Of the Volumetric Sweep Efficiency During Sg Dag And Tag Injectionsmentioning
confidence: 99%
“…The gas always extracts some components from the oil phase (Boyun et al 2007). Therefore, the efficiency of oil transport by gas can be explained by the concept of MMP (Wang et al 2020). When the gas injection is maintained above the MMP, a high oil recovery factor is achieved (Bisweswar et al 2020).…”
Section: Results Of Comparative Simulation Of the Volumetric Sweep Efficiency During Sg Dag And Tag Injectionsmentioning
confidence: 99%
“…Global warming and insufficient energy supply have aroused interest in enhanced oil recovery (EOR) with CO 2 and CO 2 capture, utilization and storage (CCUS). Injection of CO 2 into oil reservoirs known as CO 2 -enhanced oil recovery (EOR) can not only help to store the CO 2 but also improve the recovery of crude oil. Hence, this process is considered to be the most cost-effective CCUS technique and has been widely used in the development of oilfields. , In CO 2 injection EOR projects, CO 2 diffuses into the formation and helps improve oil recovery by reducing the crude oil viscosity, supplementing the formation energy, swelling oil volume, and reducing the interfacial tension. , Studies have shown that the in situ mass transfer between CO 2 and heavy oil under reservoir conditions is dominated by molecular diffusion and dispersion. , The magnitude of molecular-diffusion coefficients affects the time for the heavy oil to achieve desirable viscosity reduction and swelling effect, thus influencing the oil-production response. , Therefore, the determination of CO 2 diffusion coefficient has extremely important guidance on CO 2 -EOR risk assessment, engineering design, and economic evaluation. , …”
Section: Introductionmentioning
confidence: 99%
“…9,10 In CO 2 injection EOR projects, CO 2 diffuses into the formation and helps improve oil recovery by reducing the crude oil viscosity, supplementing the formation energy, swelling oil volume, and reducing the interfacial tension. 11,12 Studies have shown that the in situ mass transfer between CO 2 and heavy oil under reservoir conditions is dominated by molecular diffusion and dispersion. 13,14 The magnitude of molecular-diffusion coefficients affects the time for the heavy oil to achieve desirable viscosity reduction and swelling effect, thus influencing the oil-production response.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many newly discovered low-permeability reserves are poorly developed, resulting in a huge potential of remaining reserves in unproduced beach-bar sand reservoirs. For ultra-low permeability beach-bar sand reservoirs, water flooding development is greatly restricted (Li et al, 2020;Mahmud et al, 2020;Wang et al, 2020;Li., 2022;Wang et al, 2022). The development method that relies solely on elastic energy results in rapid decline in production and low recovery of crude oil.…”
Section: Introductionmentioning
confidence: 99%